Life-Cycle Preferences Revisited - Antoine Bommier (ETH Zurich, CER-ETH - Center of Economic Research, 2011)
An axiomatic construction for lifecycle preferences accounting for the finiteness and the randomness of life duration is provided. We emphasize the role of intertemporal correlation aversion and explain why multiplica- tive preferences provide an interesting alternative to additive preferences, allowing to separate risk aversion from intertemporal elasticty of substitu- tion. Implications regarding the shape of the optimal consumption pro?files are discussed.
Keywords: D91; 330; Intertemporal choice; Life-cycle models; Multivariate risk aver- sion; Uncertain lifetime; Lebenszyklus; Intertemporale Entscheidung; Risikoaversion; Substitutionselastizität; Nachfragetheorie des Haushalts; Theorie